An Analysis Meanings of Hapo Ana (Thanksgiving for the Birth of a Child) Ritual Speech in Raerobo Communities of Sabu Raijua Regency: English - Rohi, Trivos Ariance; Isu, Rudolof; Dewi, Ni Putu Juliani L. (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The purpose of this study was to describe the meaning contained in the Hapo Ana (thanksgiving for the birth a child) Ritual Speech in the community of Raerobo Village, Sabu Liae Subdistrict, Sabu Raijua District. The problem raised in this research is what are the meanings contained in the Hapo Ana (thanksgiving for the birth a child) Ritual Speech in the Raerobo Village community, Sabu Liae Subdistrict, Sabu Raijua District. The theory used in this research is the theory of hermeneutics. The method used by the author in assessing the meaning in the ritual speech "Hapo Ana" (thanksgiving for the birth a child) is a qualitative descriptive method. The results showed that the Hapo Ana (thanksgiving for the birth a child) ritual ceremony consisted of several stages, namely (1) Atte ahhu (cutting the umbilical cord); (2) Ketoe nyabbu (hanging the placenta); (3) Pehune ngara (naming) and (4) Hapo Ana “thaksgiving for the birth a child” (thanksgiving for the birth a child).